The Improvement of the Modified Starch—Glucomannan—Polyvinyl Alcohol Biothermoplastic Composite Characteristics With Polycaprolactone and Anhydride Maleic Acid - Harsojuwono, Bambang Admadi; Arnata, I. Wayan; Hartiati, Amna; Setiyo, Yohanes; Hatiningsih, Sayi; Suriati, Luh (Frontiers in Sustainable Food Systems, 2022)
The purpose of this study was to determine the concentrations of polycaprolactone (PCL) and anhydride maleic acid (AMA) to produce a biothermoplastic composite of modified cassava starch-glucomannan-polyvinyl alcohol (MSGPvA BtC) that meets the Indonesian National Standard (SNI) and International Bioplastic Standards such as ISO 527/1B, PCL from UK, ASTM 5336 for PLA plastic from Japan. This study measured the tensile strength ratio and Young’s modulus of MSGPvA BtC compared to commercial biothermoplastics (CBt), elongation at break, swelling, water vapor transmission rate (WVTR), and biodegradation time. In addition, the surface profile, functional group, crystallinity and thermal stability were also observed which were analyzed qualitatively and quantitatively. MSGPvA BtC with 20% PCL and 3.5% AMA was able to increase and improve tensile strength, elongation at break, Young's modulus, swelling, WVTR, and degradation time. MSGPvA BtC with 5% PCL and 0.5% AMA has a transverse surface profile that shows the presence of clear and wavy fibers, an elongated surface profile with indistinct waves, containing the OH functional group at wave numbers 2962.66 and 3448.72 cm-1, C = O at a wave number of 1735.93 cm-1 and has a low crystallinity degree but relatively high thermal stability. All MSGPvA BtC characteristics with 5% PCL and 0.5% AMA have met the Indonesian National Standard (SNI) and International Bioplastic Standards (ISO 527/1B, PCL from England, ASTM 5336 for PLA plastic from Japan), except for swelling characteristics. Thus MSGPvA BtC with 5% PCL and 0.5% AMA has the potential to be used as food packaging material.